Images of Korea - Korea Foundation (Seoul : Korea Foundation, 1992)
Traditions and customs of Korea are shown. They include daily life, traditional costumes, festivals, games, and art
Title on container
H-71023
VHS format
Keywords: Costume -- Korea; Dance -- Korea; Music -- Korea; Pottery, Korean; Korea (South) -- Civilization